Adsorption of heavy metal ions by various low-cost adsorbents: a review. Issue 2 (26th January 2022) - Chakraborty, Rupa; Asthana, Anupama; Singh, Ajaya Kumar; Jain, Bhawana; Susan, Abu Bin Hasan
ABSTRACT: Environmental pollution, particularly from heavy metal ions in the wastewater, is one of the most serious concerns of the world. In the pursuit of remedial action, various conventional methods such as ion exchange, chemical precipitation, coagulation, membrane separation, reverse osmosis, and adsorption methods have so far been used for the removal of heavy metal ions. A good variety of adsorbents have been developed to remove different heavy metal ions from wastewater in particular those which have been detrimental to living organisms. Adsorption processes have been very demanding for high removal efficiency of heavy metal ions even at trace levels and they are low cost as compared to conventional methods. It has therefore been crucial to develop low cost and readily available adsorbents for the adsorption of heavy metal ions from wastewater. The adsorbents may be collected from agricultural and animal waste and industrial by-products. All adsorbents, by their intrinsic nature, have functional groups to play the key role in metal ion adsorption. Generally, chemically modified adsorbents enhance the surface area of the adsorbent and exhibit higher adsorption capacity than unmodified adsorbents. In this review, a series of natural waste materials and their modified forms have been evaluated for the removal of various metals from potable and wastewater. The major focus has been an accumulation of comprehensive knowledge on of the use of the low-cost adsorbents for removal of heavy metal ions.